2015
DOI: 10.1063/1.4935573
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide is tightly bound in the [Co(Pyridine)(CO2)]− anionic complex

Abstract: The [Co(Pyridine)(CO2)](-) anionic complex was studied through the combination of photoelectron spectroscopy and density functional theory calculations. This complex was envisioned as a primitive model system for studying CO2 binding to negatively charged sites in metal organic frameworks. The vertical detachment energy (VDE) measured via the photoelectron spectrum is 2.7 eV. Our calculations imply a structure for [Co(Pyridine)(CO2)](-) in which a central cobalt atom is bound to pyridine and CO2 moieties on ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…The NPA method has been found to be satisfactory in calculating the charge distribution within a cluster. [27][28][29][30][31][32][33]…”
Section: Experimental and Theoretical Methodsmentioning
confidence: 99%
“…The NPA method has been found to be satisfactory in calculating the charge distribution within a cluster. [27][28][29][30][31][32][33]…”
Section: Experimental and Theoretical Methodsmentioning
confidence: 99%
“…Recently, to gain fundamental insight into the metal–CO 2 interactions, the structures of various anionic complexes [M­(CO 2 ) n ] − (M = Co, Ni, Cu, Ag, and Au) have been studied by infrared (IR) spectroscopy and photoelectron spectroscopy (PES) with the help of density functional theory (DFT) calculations. The structural motifs of [M­(CO 2 ) n ] − vary significantly between noble metals (Cu, Ag, Au) and open-d-shell metals (Co, Ni). Metalloformate-like complexes [M–CO 2 ] − , in which CO 2 is bound to M via the C atom with typical energies of 0.2–0.4 eV, are formed as stable units for M = Cu, Ag, and Au. , The CO 2 ligand is reductively activated by partial electron transfer from M; the excess charge on CO 2 is reduced in the order of Cu > Ag > Au, reflecting the electronegativity of the metal atom.…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 as a ligand was also investigated as metal oxides, NbO 2 + (CO 2 ) n and TaO 2 + (CO 2 ) n by Mackenzie and co‐workers . Photoelectron spectroscopy by the Bowen group revealed CO 2 activation upon attachment to anionic cobalt pyridine complexes and provided a different look on anionic coinage metal complexes with CO 2…”
Section: Introductionmentioning
confidence: 99%
“…[4,52] CO 2 as al igand was also investigated as metal oxides, NbO 2 + (CO 2 ) n and Ta O 2 + (CO 2 ) n by Mackenzie and co-workers. [53] Photoelectron spectroscopy by the Bowengroup revealed CO 2 activation upon attachment to anionic cobalt pyridine complexes [54] and providedadifferent look on anionic coinage metal complexes with CO 2 . [55] The above-mentionedI Rs tudy of Co(CO 2 ) n À showed that Co forms ac ore with two negatively charged CO 2 molecules attached via ab identate motif, formingatwisted butterfly arrangement.…”
Section: Introductionmentioning
confidence: 99%